PERUBAHAN SOSIAL DAN GUNCANGAN BUDAYA (Suatu Kajian Sosiologis Terhadap Perubahan Sosial Pada Masyarakat Pulau Nusalaut, Kecamatan Nusalaut, Kabupaten Maluku Tengah) - Lucas Molle; Rido Dominggus Latuheru; Diana Christina Nikolebu (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
Changes in social, economic systems, or religious systems usually have a wide impact on people's lives such as culture shock, loss of self-identity, and social conflicts. However, society may see change as a challenge that can develop a variety of potential strengths. Social change usually occurs when people are not satisfied with the existing conditions, changes can occur spontaneously, but also because they are planned, the process of social change does not always lead society to decline, but also leads society towards progress. Changes like this also occurred on Nusalat Island, Central Maluku Regency, after Nusalaut Island was separated from Saparua District and became a separate sub-district since 2004 where the sub-district city is in the State of Ameth. Various problems that have occurred on the island of Nusalaut since being separated from the Saparua sub-district until this moment, there have been many changes in the community on the island of Nusalaut and one of the biggest triggers is the mobilization of residents from urban areas, because urban communities not only deliver their bodies but also along with their culture. the problem is what about the local community (the people of Nusalaut), do the people of Nusalaut maintain the local culture, and ignore the foreign culture?; do the people of Nusalaut mix local culture with foreign culture?; Or do the people of Nusalaut accept foreign culture and ignore local culture?. This question became mysterious, feared that the people of Nusalaut would lose their identity as a child of the country and there would be a massive cultural shock. This is because the real condition that occurs on the island of Nusalaut is that until now the way of life of the brothers has shifted, everything is valued in money. the older generation always maintains the values of the basudara people, while the younger generation looks for their own foothold. In addition, the manners/ethics of speech and manners of dressing by the younger generation are no longer controlled; the habit of greeting each other when passing each other also experienced a shift, this could lead to conflict between the older generation and the younger generation. However, the process of change does not always lead society in a negative direction, there is also a process of change that leads society in a positive direction, for example: transportation and communication become smooth, the equipment system begins to change, which used to still use human power, but in the present condition everything uses machine power. . This is a form of social change, it does not always lead society in a negative direction, but also leads society in a positive direction.